Marketing Cost of Wheat at Different Marketing Places in Haryana - Dagar, Anita; Kumar, Sandeep (Indian Journal of Marketing, 2012)
Wheat has to undergo a series of transfers or exchange (channels) from one hand to another before it finally reaches the consumer. Keeping in view all transfers and channels involved in the marketing of wheat, an attempt has been made in the present paper to examine the marketing cost and its components and the share of marketing cost in the total sales at different marketing places by small, medium and large size farmers in Sirsa, Haryana in relation to the primary marketing channel i.e. from farmers to purchasers. The results of the study are based on primary as well as secondary data. The study concluded that a large amount of wheat was sold outside the village as compared to inside the village. Out of different cost components, the transportation cost comprised of a major share in the total marketing cost inside the village, and the agents' charges comprised of a major chunk of the total marketing cost outside the village. The paper also presents some useful suggestions to reduce the marketing cost of wheat both inside and outside the village.